Growth parameter design for homogeneous material composition in ternary GaxIn1−xP nanowires. (7th October 2015) - Berg, Alexander; Lenrick, Filip; Vainorius, Neimantas; Beech, Jason P; Wallenberg, L Reine; Borgström, Magnus T
Abstract: Ternary nanowires (NWs) often exhibit varying material composition along the NW growth axis because of different diffusion properties of the precursor molecules. This constitutes a problem for optoelectronic devices for which a homogeneous material composition is most often of importance. Especially, ternary GaInP NWs grown under a constant Ga–In precursor ratio typically show inhomogeneous material composition along the length of the NW due to the complexity of low temperature precursor pyrolysis and relative rates of growth species from gas phase diffusion and surface diffusion that contribute to synthesis of particle-assisted growth. Here, we present the results of a method to overcome this challenge by in situ tuning of the trimethylindium molar fraction during growth of ternary Zn-doped GaInP NWs. The NW material compositions were determined by use of x-ray diffraction, scanning transmission electron microscopy and energy dispersive x-ray spectroscopy and the optical properties by photoluminescence spectroscopy.